Developing an automation-compatible quantitative and functional assay for the assessment of pluripotency - Flatt, Luke (2017)
Many of the protocols utilized in human pluripotent cell (hPSC) culture remain far from standardized from laboratory to laboratory. Lack of standardization and the knock-on effects of variable culture systems can have dramatic effects on the genetic and epigenetic status of in vitro cultured pluripotent stem cells (Miura et al, 2009; Kruta et al, 2014). Moves to create more defined culture systems have addressed matrices, culture medium (Chen et al, 2011) and dissociation agents (Terstegge et al, 2007), all with the aim of refining the protocols utilized whilst maintaining pluripotency. Similar refinement in differentiation approaches through the removal of serum, or other xenogeneic products, and utilization of chemically synthesized small molecule compounds also became an area of focus in recent years.